2014
DOI: 10.1016/j.stem.2014.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Gene Correction Minimally Impacts Whole-Genome Mutational Load in Human-Disease-Specific Induced Pluripotent Stem Cell Clones

Abstract: SUMMARY The utility of genome editing technologies for disease modeling and developing cellular therapies has been extensively documented, but the impact of these technologies on mutational load at the whole-genome level remains unclear. We performed whole-genome sequencing to evaluate the mutational load at single-base resolution in individual gene-corrected human induced pluripotent stem cells (hiPSCs) clones in three different disease models. Single-cell clones gene correction by helper-dependent adenoviral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
127
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(134 citation statements)
references
References 35 publications
6
127
0
1
Order By: Relevance
“…However, all of the discovered mutations were far removed from any predicted CRISPR gRNA1 off-target sites. It is possible that these mutations are located near cryptic off-target sites that are not predicted in silico as similar results associated with zinc finger nuclease and transcription activator-like effector nuclease have been reported (32)(33)(34). These results showed that the mutation load to the exome was minimal and that the method was clinically feasible, possibly paving the way for future clinical use.…”
Section: Discussionsupporting
confidence: 69%
“…However, all of the discovered mutations were far removed from any predicted CRISPR gRNA1 off-target sites. It is possible that these mutations are located near cryptic off-target sites that are not predicted in silico as similar results associated with zinc finger nuclease and transcription activator-like effector nuclease have been reported (32)(33)(34). These results showed that the mutation load to the exome was minimal and that the method was clinically feasible, possibly paving the way for future clinical use.…”
Section: Discussionsupporting
confidence: 69%
“…Early passage (passage 4) was used to reduce possible mosaic genotypes acquired during the passaging process [25][26][27]. The reprogramming process can also introduce mutations [28].…”
Section: Exome Sequencingmentioning
confidence: 99%
“…To analyze all coding-gene mutations, wholeexome sequencing was performed on hiPSCs following 0.4-Gy g-radiation compared with no radiation. Early passage 4 hiPSCs were used to avoid possible mosaic genotypes acquired during passaging [25][26][27][28]. Sorting and clonal expansion from single cells in parallel was used to isolate individual mutations (Fig.…”
Section: Ldi Does Not Lead To Mutagenic Events In Human Pscsmentioning
confidence: 99%
“…Good news for research groups advocating nuclease-based gene therapy came in the form of recent publications that appeared in the July 2014 issue of Cell Stem Cell by three independent labs, which conclude that targeted gene editing technologies such as the CRISPR/Cas system, helper-dependent adenoviral vectors (HDAdVs) and transcription activator-like effector nuclease (TALEN) produce low levels of unwanted off-target mutagenesis [6][7][8]. The comprehensive evaluation of nuclease-based targeted genome editing in the whole genome mutational load indicates that unwanted mutations are very rare, if there are any at all, and certainly helps ease concerns for their application in clinical settings.…”
mentioning
confidence: 99%
“…In this case, HDAdV vectors are attractive due to their ability to deliver long homology arms together with other CRISPR/Cas9 components into human cells [12]. Indeed, a recent report demonstrated the efficacy of a novel and efficient hybrid vector combining the advantages of both HDAdVs and TALENs in editing human cells in vitro [6], which paves the way to develop more powerful, efficient and versatile human-specific in vivo genome editing tools based on HDAdVs and Cas9 in the near future. Achieving this goal will greatly facilitate the progress of human disease study and gene therapies.…”
mentioning
confidence: 99%